2017
DOI: 10.1177/0145482x1711100309
|View full text |Cite
|
Sign up to set email alerts
|

Oral Braille Reading Decoding Strategies of Middle School Students who Are Blind or Have Low Vision

Abstract: Individualized meaningcentered approach to braille literacy education (I-M-ABLE) case study: Ajay's story.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
(7 reference statements)
0
5
0
Order By: Relevance
“…This approach is also carried out in the aspect of writing, but it has not been seen that there is a development in Ajay's writing ability, so that later research is expected to focus on aspects of writing the subject so that it can develop in a balanced manner. Savaiano, et al [11] Media The results of the above study note that children's abilities different. This is in accordance with the level of ability of each child, so that further research can consider the child's initial ability so that they choose ways, methods and media that are suitable for each child's condition.…”
Section: Resultsmentioning
confidence: 69%
“…This approach is also carried out in the aspect of writing, but it has not been seen that there is a development in Ajay's writing ability, so that later research is expected to focus on aspects of writing the subject so that it can develop in a balanced manner. Savaiano, et al [11] Media The results of the above study note that children's abilities different. This is in accordance with the level of ability of each child, so that further research can consider the child's initial ability so that they choose ways, methods and media that are suitable for each child's condition.…”
Section: Resultsmentioning
confidence: 69%
“…Therefore, although I think that having lack of vision leads me to the difficulties to understand reading materials, description from other people is essential to enhance my understanding toward something". It was reported that there was a gap in reading rate between Braile readers and printing readers (Nannemann et al, 2017). Printing readers can read two times quicker than Braile readers.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Having limited access to reading span may lead to blind learners' difficulties to understand their reading materials. It is also suggested that Braille readers used sounded words, which might help learners use their listening capability to understand printing words and have quicker reading rates (Nannemann et al, 2017).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…For example, students with visual impairments can learn science through appropriate methods if given the proper facilities (Ediyanto & Kawai, 2019). Learning media, such as assistive computer-based technology (Johnstone, Altman, Timmons, & Thurlow, 2009, Azeta, Inam, & Daramola, 2018, Eligi & Mwantimwa, 2017), verbal communication and physical help (Suveren-Erdogan & Suveren, 2018, orientation, and mobility skills (Arslantekin, 2017), and Braille (Mobaraki, Nazarloo & Toosheh, 2017, Nannemann, Bruce, Hussey, Vercollone, & McCarthy, 2017 can also help these students to understand many concepts. Furthermore, students with autism spectrum disorder can learn science through useful strategic mathematics (Su, Lai, & Rivera, 2012), computer-based interventions (Aliee, Jomhari, Rezaei, & Alias, 2013), Science eText (Knight, Wood, Spooner, Browder, & O'Brien, 2015), and the touch math technique (Yikmis, 2016).…”
Section: Discussionmentioning
confidence: 99%